Compliance in Type 2 Diabetic Patients Treated with SGLT2 Inhibitors in a Tertiary Care Hospital Peshawar Pakistan (Medical Forum Monthly, 2024)
Objective: To evaluate the adherence to treatment in type 2 diabetic patients using SGLT2 inhibitors.Study Design:Place and Duration of Study: This study was conducted at the Department of Medicine, Khyber Teaching Hospital Peshawar from August 2018 to January 2019.Materials and Methods: Total 260 diabetic patients, with mean age of 47±1.26 years, were enrolled in the study by non–probability consecutive sampling. After taking informed consent and recording the demographic profile of the patients,SGLT2 inhibitors were given for the treatment of T2DM. Necessary data was collected regarding the compliance of patients to these drugs after 2 months. The statistical analysis was done using SPSS version 20.0 and graph were constructed with graphpad prism software.Results: In total 260 patients, 182 (70%) were male and78 (30%) were female. Poor compliance (adherence to therapy) was recorded in 60 (23.07%) of patients, while in 200 (76.93%) patients shows good drug compliance. No significant association was observed in patients’ compliance with different age group. Similarly, gender makes no difference in compliance to treatment however, female patients shows slightly increase noncompliance as compared to males with OR, 95%CI 1.07(0.55-2.08). Polyuria was the main adverse event for noncompliance of the patient to SGLT-2 inhibitors.Conclusion: Compliance to SGLT-2 inhibitors in our study in 76.93% which may be increased by proper counselling the patients. Furthermore, multiple studies may be conducted with large sample size to further strengthen our findings and to identify other adverse events as well.